Natural Fibers Density Measurement Methods: Factors Affecting Density Result in Helium Gas Pycnometry - Abebayehu Abdela; Mieraf Asfaw; Bart Buffel; Belete Sirahbizu; Frederik Desplentere (Journal of Natural Fibers)
Fiber density can be used to estimate composite weight and to evaluate fiber content for property predictions in fiber-reinforced composites. Yet, natural fibers don’t have fixed density value given on datasheet and their density measurement is affected by various factors. This study compares various standard natural fiber’s density mearusing methods and identifies determinant factors to, then, estimate the density of Enset fibers by using the optimal combination. The advantages and disadvantages of five standard methods were compared considering the characteristics of natural fibers’ and methods’ effectiveness where Helium gas Pycnometry is selected afterward. Standard calibration sphere and synthetic fiber with known density is measured for validation. The study analyzed the impact of variables on result’s precision and accuracy. Then, Density of Enset fiber have been measured with varied factors including uniformity and duration purging, volume cell type and amount of fiber in a cell, and fiber size. The result showed that fluctuation is minimized, and accuracy and precision is enhanced for the larger volume cell, larger mass of fiber in a cell, smaller size fiber and longer uniform purging. Finally, measured density of Enset using the best combination of factors is 1.38 ± 0.01 g/cm3.